2019
DOI: 10.3389/fendo.2019.00726
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Stearoyl-CoA 9-Desaturase 1 Protects Human Mesenchymal Stromal Cells Against Palmitic Acid-Induced Lipotoxicity and Inflammation

Abstract: In bone diseases such as osteonecrosis and osteoporosis, a shift toward a preferential differentiation of mesenchymal stromal cells (MSC) into adipocytes at the expense of the osteoblastic lineage is described, leading to excessive accumulation of adipocytes in the bone marrow of the patients. The influence of cytokines and adipokines secreted by adipocytes on skeletal health is already well-documented but the impact of free fatty acids release on bone cell biology and viability is an emerging concept. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 71 publications
(102 reference statements)
2
21
0
Order By: Relevance
“…The outstanding toxicity of saturated FAs is often explained by the reluctance of the cells to process fully saturated DGs, and by the consequent ineffectiveness of channeling the saturated acyl-CoA surplus towards TG synthesis [21]. The theory that unsaturated FAs attenuate palmitate toxicity by facilitating TG synthesis is supported by experimental data obtained in certain cell types, such as CHO cells and primary mouse embryonic fibroblasts [22], mouse myoblasts [23], human mesenchymal stromal cells and osteoblasts [18]. Nevertheless, a palmitate treatment was used in HepG2 hepatocarcinoma cells [17] and controversial data have been published as to the deleterious or protective role of TG deposition in β-cell lipotoxicity [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outstanding toxicity of saturated FAs is often explained by the reluctance of the cells to process fully saturated DGs, and by the consequent ineffectiveness of channeling the saturated acyl-CoA surplus towards TG synthesis [21]. The theory that unsaturated FAs attenuate palmitate toxicity by facilitating TG synthesis is supported by experimental data obtained in certain cell types, such as CHO cells and primary mouse embryonic fibroblasts [22], mouse myoblasts [23], human mesenchymal stromal cells and osteoblasts [18]. Nevertheless, a palmitate treatment was used in HepG2 hepatocarcinoma cells [17] and controversial data have been published as to the deleterious or protective role of TG deposition in β-cell lipotoxicity [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the obvious difference between the cell damage caused by saturated and unsaturated FAs, the potentially protective effect of oleate against palmitate toxicity has also drawn growing attention in the past few years. Simultaneously added oleate alleviated palmitate induced toxicity in various cells, including hepatocytes and hepatoma cells [17], human mesenchymal stromal cells and osteoblasts [18], and also decreased non-alcoholic steatohepatitis (NASH) injury in rats with high fat diets [17]. Most importantly, it has been shown that co-administration of oleate can prevent palmitate-induced activation of the unfolded protein response (UPR) in β-cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, its deficiency is also associated with a narrow eye fissure [22] and skin abnormalities [17]. Recently, it has been demonstrated that SCD1 protects against the palmitate-induced cytotoxic effect in mesenchymal stromal cells and osteoblasts [23]. SCD1 modifies the SFA/MUFA ratio through its catalytic activity and induces caspase 3/ activation, endoplasmic reticulum (ER) stress, and inflammation [23] (Figure 2).…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
“…Recently, it has been demonstrated that SCD1 protects against the palmitate-induced cytotoxic effect in mesenchymal stromal cells and osteoblasts [23]. SCD1 modifies the SFA/MUFA ratio through its catalytic activity and induces caspase 3/ activation, endoplasmic reticulum (ER) stress, and inflammation [23] (Figure 2). SCD1 overexpression is mediated by LXRs, peroxisome proliferator-activated receptors (PPARs), sterol regulatory element-binding proteins (SREBPs), CCAAT/enhancer-binding proteins (C/EBP)α, etc.…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
See 1 more Smart Citation